Summertime ozone production at Carlsbad Caverns National Park, New Mexico: influence of oil and natural gas development - Marsavin, Andrey, author; Collett, Jeffrey L., Jr., advisor; Fischer, Emily V., committee member; Willis, Megan D., committee member (Colorado State University. Libraries, 2023)
Southeastern New Mexico's Carlsbad Caverns National Park (CAVE) has increasingly experienced summertime ground-level ozone (O3) levels surpassing the US Environmental Protection Agency's National Ambient Air Quality Standard (NAAQS) of 70 parts per billion by volume (ppbv). The park is located in the western part of the Permian oil and natural gas (O&G) basin, where production rates have more than tripled in the last decade. We investigate O3–precursor relationships by constraining a zero-dimensional (0-D) model to an hourly nitrogen oxides (NOx = NO + NO2) and speciated volatile organic compound (VOC) data set collected at CAVE during the summer of 2019. O&G-related VOCs dominated the calculated VOC reactivity with hydroxyl radicals (OH) on days when O3 concentrations were primarily controlled by local photochemistry. Radical budget analysis showed that NOx levels were high enough to impose VOC sensitivity on O3 formation in the morning hours, while subsequent NOx loss through photochemical consumption led to NOx-sensitive conditions in the afternoon. Daily maximum O3 was sensitive to both NOx and O&G-related VOC emission reductions, with NOx reductions generally being more effective. The model could not reproduce a 5-day high O3 episode when constrained to observed NOx and primary VOCs, likely due to influence from O3 produced during air mass transport from regional O&G basins as indicated by back-trajectory analysis, low i/n-pentane ratios consistent with O&G emissions, increased concentrations of secondary VOCs, and extensive oxidation of emitted NOx. Constraining the model with observed total oxidized reactive nitrogen (NOy), which approximates NOx at the time of emission, greatly improves model-observation agreement during this episode, reaffirming NOx-sensitive conditions in photochemically aged air masses.
Keywords: ground-level ozone; oil and natural gas extraction; national parks; air quality